Dioscorea bulbifera Mediated Synthesis of Novel AucoreAgshell Nanoparticles with Potent Antibiofilm and Antileishmanial Activity. (22nd April 2015) - Ghosh, Sougata; Jagtap, Soham; More, Piyush; Shete, Usha J.; Maheshwari, Neeraj O.; Rao, Shilpa J.; Kitture, Rohini; Kale, Sangeeta; Bellare, Jayesh; Patil, Shivprasad; Pal, Jayanta K.; Chopade, Balu A.
Abstract : Dioscorea bulbifera is a potent medicinal plant used in both Indian and Chinese traditional medicine owing to its rich phytochemical diversity. Herein, we report the rapid synthesis of novel Au core Ag shell nanoparticles by D. bulbifera tuber extract (DBTE). Au core Ag shell NPs synthesis was completed within 5 h showing a prominent peak at 540 nm. HRTEM analysis revealed 9 nm inner core of elemental gold covered by a silver shell giving a total particle diameter upto 15 nm. Au core Ag shell NPs were comprised of 57.34 ± 1.01 % gold and 42.66 ± 0.97 % silver of the total mass. Au core Ag shell NPs showed highest biofilm inhibition upto 83.68 ± 0.09 % against A. baumannii . Biofilms of P. aeruginosa, E. coli, and S. aureus were inhibited up to 18.93 ± 1.94 %, 22.33 ± 0.56 %, and 30.70 ± 1.33 %, respectively. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) confirmed unregulated cellular efflux through pore formation leading to cell death. Potent antileishmanial activity of Au core Ag shell NPs (MIC = 32   µ g/mL) was confirmed by MTT assay. Further SEM micrographs showed pronounced deformity in the spindle shaped cellular morphology changing to spherical. This is the first report of synthesis, characterization, antibiofilm, and antileishmanial activity of Au core Ag shell NPs synthesized by D. bulbifera .